2004
DOI: 10.1074/jbc.m402254200
|View full text |Cite
|
Sign up to set email alerts
|

Coassembly of Big Conductance Ca2+-activated K+ Channels and L-type Voltage-gated Ca2+ Channels in Rat Brain

Abstract: Based on electrophysiological studies, Ca 2؉ -activated K ؉ channels and voltage-gated Ca 2؉ channels appear to be located in close proximity in neurons. Such colocalization would ensure selective and rapid activation of K ؉ channels by local increases in the cytosolic calcium concentration. The nature of the apparent coupling is not known. In the present study we report a direct coassembly of big conductance Ca 2؉ -activated K ؉ channels (BK) and L-type voltage-gated Ca 2؉ channels in rat brain. Saturation im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 30 publications
(28 reference statements)
8
79
2
Order By: Relevance
“…1Ai) showed that Ca V 1.2 immunoreactivity was 45% weaker than Ca V 2.2 immunoreactivity. This weak interaction between L-type Ca 2+ and BK channels was reminiscent of the co-IP data reported by Grunnet and Kaufmann (Grunnet and Kaufmann, 2004). Thus, the data clearly indicated that the two channel subunits could associate in rat brain, but the association was more prevalent between Ntype Ca 2+ and BK channels.…”
Section: Association Of L-type Casupporting
confidence: 57%
See 2 more Smart Citations
“…1Ai) showed that Ca V 1.2 immunoreactivity was 45% weaker than Ca V 2.2 immunoreactivity. This weak interaction between L-type Ca 2+ and BK channels was reminiscent of the co-IP data reported by Grunnet and Kaufmann (Grunnet and Kaufmann, 2004). Thus, the data clearly indicated that the two channel subunits could associate in rat brain, but the association was more prevalent between Ntype Ca 2+ and BK channels.…”
Section: Association Of L-type Casupporting
confidence: 57%
“…Using reciprocal co-immunoprecipitation, we found that N-type channels were more abundantly associated with BK channels than L-type channels (Ca V 1.2) in rat brain. Expression of only the pore-forming ␣-subunits of the N-type (Ca V 2.2) and BK (Slo 27 ) channels in a non-neuronal cell-line gave robust macroscopic currents using biochemical techniques to demonstrate the association of L-type and BK channels in rat whole brain (Grunnet and Kaufmann, 2004;Berkefeld et al, 2006). However, no study has yet identified the rapid functional coupling between BK and Ca 2+ channels and resolved how this might be achieved.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The C-DEC splice variant generates an extended C terminus resulting in BK␣ with enhanced retention of newly synthesized BK Ca channels in the endoplasmic reticulum, which finally results in decreased cell surface expression (60,61). BK Ca channels are robustly expressed in mammalian central neurons (62,63) and are predominantly localized to axons and presynaptic terminals (17,37) but are also present in certain neuronal somata and dendrites (18,64). In rat brain, BK␣ splice variants may be differentially expressed in distinct cell types or different compartments of the same neuron.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Ca 2ϩ influx via L-type VDCCs is a requirement for the potassium current inhibited by Prl in the HV range. In neurons, BK channels often colocalize to microdomains with L-type Ca 2ϩ channels (Grunnet and Kaufmann, 2004;Berkefeld et al, 2006;Fakler and Adelman, 2008), and Ca 2ϩ influx through the latter is believed to shift BK voltage dependence to more hyperpolarized potentials. The tight coupling of L-type VDCCs to BK channels has been implicated in other endocrine and neuroendocrine cells with sustained secretion in response to steady depolarization (Prakriya and Lingle, 1999;Marcantoni et al, 2007Marcantoni et al, , 2010 and, in adrenomedullary cells, can be recruited as demands on hormone release increase (Polo-Parada et al, 2006).…”
Section: Discussionmentioning
confidence: 99%